Rediscovery of Tulipa sylvestris subsp. primulina (Baker) Maire & Weiller in the Belezma National Park (north-eastern Algeria) - Maalem, Nour El Houda; Belkassam, Abdelouahab; Zekri, Jihane; Gordo, Belkacem (Biodiversity: Research and Conservation, 2023)
In the spring of 2022, botanical surveys carried out in the Belezma National Park allowed the rediscovery of Tulipa sylvestris subsp. primulina, a rare and endemic Algerian-Moroccan species. The provided photographs as well as an accurate description of the plant facilitate its identification. The added map shows its distribution throughout Algeria.